Smartphone Warning System untuk Peringatan Kunci Kontak yang Tertinggal pada Kendaraan Motor Roda Dua - Zulkarnain Zulkarnain; Riyanto Setiyono; Ferry Ariessahi (Fakultas Teknik Universitas Langlangbuana, 2018)
In the level of activity of society will work leads to a lack of attention and security will be the key vehicle, need a device or system that is capable of providing reminders and detail reports and updates. In this case, monitoring of vehicles do with a motorcycle at a considerable distance. On this occasion the author will design and build a motorcycle alarm system using infrared sensors and neoway m590e gsm module, the working principle of this system is that if a vehicle ignition key is inserted into the ignition key, the sensor will detect the key attached. The sensor sends a signal to the switch contacts that are in the off condition resulting data input logic 0 to Arduino, the Arduino programmable timer which starts counting for 10 seconds. At the time of the count has been exhausted, the Arduino will transmit data signals to turn on the alarm and gsm module to be received through the mobile application, until the conditions in the state of the vehicle ignition is on or the key is removed. Preprogrammed alarm will be back in its original state.